Promotion of new local sports media (Dunia Sukan) / Mohammad Haris Naim Adam - Naim Adam, Mohammad Haris (Faculty of Art and Design, 2013)
The promotion of Dunia Sukan Media & Event Company is the issue of the topic. The problem is, in Malaysia there’s not much local media that providing the full information and news about local sports development. Consequently, people in Malaysia were not interested anymore into getting news about local sports than the overseas. So, the purpose of this research is to get a best way to promote DS Media to the local sports lover as the best local sports media in Malaysia that providing the information that needed to develop the sports industry in Malaysia. The findings show that overall the result agrees that Malaysian still interested of local sports and the needed of the media to function as they should to develop the Malaysian sports industry.